Pelatihan Analisis Strategi Permainan Futsal melalui Media Video bagi Siswa MAN 4 Bone - Mohammad Dika Raswadi; Fatoni Fatoni; Andi Ihsan; Irvan Irvan; Tri Angriawan (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
Futsal extracurricular activities in secondary schools generally focus on mastering basic techniques, while understanding game strategy has not received optimal attention. This condition has an impact on students' limited ability to read game situations and make appropriate decisions. This Community Service activity aims to improve the understanding of futsal game strategy through video-based analysis training for students of MAN 4 Bone. The implementation method uses a participatory training and mentoring approach that includes the presentation of futsal strategy concepts, match video analysis, group discussions, and simulations of strategy implementation on the field. The activity participated in 30 students who are members of the futsal extracurricular. The results of the activity showed an increase in students' understanding of aspects of game formations, offensive and defensive transitions, and game decision-making. In addition, the level of student participation during the activity was high and the quality of the game became more structured. This activity proves that video media is effective as a learning tool for futsal strategy and has the potential to be developed as an innovative and sustainable model for school futsal development.